2020
DOI: 10.1016/j.jobcr.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of bone marrow-derived mesenchymal stem cells on the parotid glands of streptozotocin induced diabetes rats

Abstract: Background: The functional insufficiency of salivary glands constitute the common oral complaints in both type 1 and type 2 diabetes mellitus. The treatment with stem cell could decrease diabetic-induced hyposalivation and improve the quality of life for patients. Objective: The current study designed to assess the biological outcome of systemic injection of stem cells on the parotid salivary gland in streptozotocin induced diabetic. Methods: Twenty-four albino rats received intra-peritoneal injection of 50 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In the context of this study's objective regarding the role of BMDSc on parotid glands of STZ‐induced diabetes rats, the statistical analysis of blood glucose levels revealed significant differences among the groups, confirming a reduction in blood glucose levels post‐BMDSc injection. This observation aligns with Fotino et al's findings, suggesting that BM‐MSC‐derived stem cell transplantation holds promise for tissue repair, regeneration, and immune response stimulation 30,31 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the context of this study's objective regarding the role of BMDSc on parotid glands of STZ‐induced diabetes rats, the statistical analysis of blood glucose levels revealed significant differences among the groups, confirming a reduction in blood glucose levels post‐BMDSc injection. This observation aligns with Fotino et al's findings, suggesting that BM‐MSC‐derived stem cell transplantation holds promise for tissue repair, regeneration, and immune response stimulation 30,31 …”
Section: Discussionsupporting
confidence: 87%
“…This observation aligns with Fotino et al's findings, suggesting that BM-MSC-derived stem cell transplantation holds promise for tissue repair, regeneration, and immune response stimulation. 30,31 In recent years, gene therapy has emerged as a potential treatment for diabetes. Lee et al 32 utilized a recombinant adeno-associated virus to deliver a single-chain insulin analog to the liver of diabetic rats induced by STZ.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MSCs interact with vascular endothelial cells to regulate inflammatory infiltration ( 44 ). On the other hand, bone marrow mesenchymal stem cells act through the release of soluble factors, so there are still many unknown areas to explore in cell therapy using mesenchymal stem cells ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…AQP5 is also downregulated in the parotid salivary gland of T2D rats that showed decreased salivary flow rate [ 138 ]. Rats treatment with bone marrow-derived stem cells improves the salivary flow rate and alters AQP5 levels in the parotid gland [ 139 ]. It was also shown that autophagy degrades AQP5 in the submandibular salivary gland [ 46 ].…”
Section: Possible Role Of Aqps “Metabolic Network” In Obesity-induced Systemic Insulin Resistancementioning
confidence: 99%